Effect of carbon residues structures on burnout characteristic by FTIR and Raman spectroscopy - Liu, Yunxia; Sun, Beilei; Tajcmanová, Lucie; Liu, Chao; Wu, Jie (Spectrochimica acta. A, Molecular and biomolecular spectroscopy, 2022)
Fly ash (-FA) from seven typical power plants in Shanxi province (North China) were collected to explore the effect of carbon residues (-CR) structures on their burnout characteristic. Burnout characteristic is expressed by the loss on ignition (LOI) content in fly ash. Raman spectroscopy and Fourier Transform infrared (FTIR) spectroscopy are used to characterize the structure of CR. The structure parameters include Raman parameter (the full width at half maxima (FWHM) ratio of D1 and G, ID1/IG) and FTIR parameter (asymmetric stretching intensity ratio of CH2 and CH3 groups, A(CH2)/A(CH3)). Three samples come from circulating fluidized bed (CFB), and four samples are from pulverized coal boilers (PC). Then two types of power plants are numbered from one to three according to the increasing degree of feed coal (-C) metamorphism. The CFB-1-FA, CFB-2-FA, and CFB-3-FA have loss on ignition (LOI) of 9.01%, 16.4%, and 21.6% respectively, while the LOI contents are 1.99%, 4.62%, 23.7%, and 5.00% for the PC-1-FA, PC-2-FA, PC-3-FA, and PC-4-FA. The results show that carbon residues in the PC fly ash mainly have the shorter and branched aliphatic side chains with lower A(CH2)/A(CH3) value. While carbon residues in the CFB fly ash have relatively longer aliphatic chains, and intramolecular aromatization is the main reaction during combustion. The ID1/IG of the CFB carbon residues are generally higher than it for the PC samples, indicating a more ordered structure. Oxygen-deficient environment and the longer residence time at temperature around 900 °C in the CFB boiler promote the ordering progress of the CR. The ordered CR suppresses its burnout and leads to an increase LOI content in fly ash. In turn, sufficient oxygen and temperature around 1200 °C in the PC boiler make the CR further oxidize and decompose. The CR become less ordered and are prone to burn out, resulting in a reduction of the LOI content.
Gesehen am 11.05.2022